Elemental tellurium mediated synthesis of 2-(trifluoromethyl)oxazoles using trifluoroacetic anhydride as reagent. Issue 76 (7th September 2018) - Luo, Beibei; Weng, Zhiqiang
Abstract : An elemental tellurium mediated synthesis of 2-(trifluoromethyl)oxazoles from the reaction of acetophenone oxime acetates with trifluoroacetic anhydride is described. Abstract : An elemental tellurium mediated synthesis of 2-(trifluoromethyl)oxazoles from the reaction of acetophenone oxime acetates with trifluoroacetic anhydride has been developed. This new tandem cyclization proceeds in good to excellent yields via a SET reduction followed by a 5- endo -trig pathway. Some of the title compounds showed fungicidal and insecticidal activities.